1992
DOI: 10.1083/jcb.118.6.1333
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic dynein participates in the centrosomal localization of the Golgi complex.

Abstract: The localization of the Golgi complex depends upon the integrity of the microtubule apparatus. At interphase, the Golgi has a restricted pericentriolar localization. During mitosis, it fragments into small vesicles that are dispersed throughout the cytoplasm until telophase, when they again coalesce near the centrosome. These observations have suggested that the Golgi complex utilizes a dynein-like motor to mediate its transport from the cell periphery towards the minus ends of microtubules, located at the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(185 citation statements)
references
References 61 publications
10
174
1
Order By: Relevance
“…Astral MTs seem indispensable for the reclustering of the organelle in a central location (Shima et al, 1998), but intermediate steps in this process might involve the capture of Golgiattached MTs in the centrosomal area to facilitate the reclustering process. Such a model would require Golgi MTs to exhibit reverse polarity or would be quite complicated in terms of molecular motor regulation, because Golgi reclustering is dynein dependent (Corthésy-Theulaz et al, 1992;Fath et al, 1994, Burkhardt et al, 1997Harada et al, 1998). This would be in a way similar to the behavior of chromosomes during mitosis because they have the possibility to directly nucleate MTs in addition to their capture by centrosomal MTs (Carazo-Salas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astral MTs seem indispensable for the reclustering of the organelle in a central location (Shima et al, 1998), but intermediate steps in this process might involve the capture of Golgiattached MTs in the centrosomal area to facilitate the reclustering process. Such a model would require Golgi MTs to exhibit reverse polarity or would be quite complicated in terms of molecular motor regulation, because Golgi reclustering is dynein dependent (Corthésy-Theulaz et al, 1992;Fath et al, 1994, Burkhardt et al, 1997Harada et al, 1998). This would be in a way similar to the behavior of chromosomes during mitosis because they have the possibility to directly nucleate MTs in addition to their capture by centrosomal MTs (Carazo-Salas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with earlier findings by Feiguin et al (1994), who found that the expression of kinesin antisense oligonucleotide rendered the Golgi apparatus more compact, microinjection of antikinesin antibodies inhibited Golgi dispersion along stable, nocodazole-resistant MTs (Minin, 1997). Conversely, the central localization of the Golgi apparatus involves cytoplasmic dynein (Corthésy-Theulaz et al, 1992;Fath et al, 1994;Burkhardt et al, 1997;Harada et al, 1998). It is also worth noting that, in addition to the kinesin-mediated disruption of the central Golgi complex during MT depolymerization, the dispersion of Golgi elements also relies on the reconstitution of mini Golgi stacks at endoplasmic reticulum (ER) exit sites (Cole et al, 1996;Storrie et al, 1998).…”
mentioning
confidence: 99%
“…Each heavy chain has two structural domains that perform distinct functions: the catalytic head domain, which contains the MgATPase and ATP-sensitive microtubule-binding activities; and the flexible dynein specialization occurs in the motor domain: all axonemal dyneins carry an outer doublet microtubule as their cargo, but each arm is specialized to generate precise mechanical force so that the dynein arms working together initiate and propagate ciliary bends (Asai and Brokaw, 1993;Brokaw, 1994). In contrast to axonemal dynein, cytoplasmic dynein carries a diverse array of molecular cargoes (Schnapp and Reese, 1989;Verde et al, 1991;Corthesy-Theulaz et al, 1992;Lin and Collins, 1992;Aniento et al, 1993;Vaisberg et al, 1993;Saunders et al, 1995;Wang et al, 1995) and is probably less specialized in force production. The current view is that cytoplasmic dynein is a homodimer of the heavy chain MAPlC (Vallee et al, 1988;Neely et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the Golgi to undergo continuous, homotypic fusion can nevertheless be monitored by live-cell video microscopy after microinjection or fusion of two cell types harboring different colored Golgi stacks. Indeed, exogenously added, wild-type Golgi complexes could receive cargo from the Golgi complexes of mutant, semiintact CHO cells (35).…”
Section: Combining Premises 1 Andmentioning
confidence: 99%